Kontribusi Perdebatan Nasab Ba’alwi dalam Pengembangan Pembelajaran Pendidikan Agama Islam - Santoso, Hadi (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2025)
This research aims to explore how the debate on the Baalwi lineage by Kyai Imaduddin can be integrated into Islamic Religious Education learning, as well as how this approach can improve teaching strategies and methods that are more relevant to the needs of students. This research uses a qualitative method with a case study approach and historical analysis carried out through literature study, namely examining Kyai Imaduddin's written works, articles, books and historical documents related to the Ba'alwi lineage debate. This research finds that the Ba'alwi nasab debate can encourage changes in Islamic Religious Education learning strategies and methods by using a more inclusive and scientifically based approach, emphasizing personal qualities and scientific contributions rather than heredity as a source of authority. The implications of this thinking can be seen in the integration of teaching materials, development of modules and textbooks, as well as learning methods such as critical discussions, case studies and reflective writing. This allows students to explore and analyze the topic of the Ba'alwi nasab debate in more depth, as well as develop critical and analytical thinking skills.